2020
DOI: 10.1038/s41396-020-0621-7
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal dynamics of the archaeal community in coastal sediments: assembly process and co-occurrence relationship

Abstract: Studies of marine benthic archaeal communities are updating our view of their taxonomic composition and metabolic versatility. However, large knowledge gaps remain with regard to community assembly processes and inter taxa associations. Here, using 16S rRNA gene amplicon sequencing and qPCR, we investigated the spatiotemporal dynamics, assembly processes, and co-occurrence relationships of the archaeal community in 58 surface sediment samples collected in both summer and winter from across~1500 km of the easte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
133
3
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(150 citation statements)
references
References 82 publications
12
133
3
2
Order By: Relevance
“…The authors pointed out that the distinct microbial communities in these two estuaries might be affected by different localized interactions, however, more thorough investigations are needed to explain such differences. Similarly, a recent report revealed seasonal variations of archaeal communities in estuarine and coastal regions ( Liu et al, 2020 ), highlighting the notion that spatiotemporal distribution of archaeal community is co-influenced by environmental parameters, including salinity and temperature. However, other than spatial and temporal variables, technical biases, such as sampling methods, library construction approaches, and different usage of primers and marker genes, might also impact the microbial community composition.…”
Section: Community Structure Of Estuarine Archaeamentioning
confidence: 78%
See 1 more Smart Citation
“…The authors pointed out that the distinct microbial communities in these two estuaries might be affected by different localized interactions, however, more thorough investigations are needed to explain such differences. Similarly, a recent report revealed seasonal variations of archaeal communities in estuarine and coastal regions ( Liu et al, 2020 ), highlighting the notion that spatiotemporal distribution of archaeal community is co-influenced by environmental parameters, including salinity and temperature. However, other than spatial and temporal variables, technical biases, such as sampling methods, library construction approaches, and different usage of primers and marker genes, might also impact the microbial community composition.…”
Section: Community Structure Of Estuarine Archaeamentioning
confidence: 78%
“…On the other hand, the pH and oxygen levels, rather than salinity, are contributing factors shaping community structure of Bathyarchaeota community structure in costal mangroves and lakes ( Yoshimura et al, 2018 ; Pan et al, 2019 , 2020 ). Further, in the southern Yellow Sea and northern East China Sea, water depth, temperature, and salinity are the most influential factors determining the distribution of Bathyarchaeota in surface sediments ( Chen Y. et al, 2020 ; Liu et al, 2020 ). Similarly, water depth is the major variable explaining the partitioned distribution pattern of Bathyarchaeota from the shallow marginal sea to the deep northern South China Sea ( Zhou et al, 2018b ).…”
Section: Bathyarchaeota In Estuariesmentioning
confidence: 99%
“…Whereas, all the K values were estimated to be positive but closer to zero (Table S2), indicating a random or convergent pattern of evolution for the phylogenetic niche conservatism relating to aforementioned traits (46,64). Accordantly, many other studies had shown that robust phylogenetic signal was related to different variables within short distances across ecosystems of diverse types (47,50,(65)(66)(67). On this basis, recent advanced quantitative ecological models (47,51,68), can be applied to compare observed between-community diversity of both phylogeny and taxonomy against a null-model, thereby quantify the relative importance of ecological processes underlying the gut microbiota in response to feed-borne bacteria.…”
Section: Quantitative Estimation Of Ecological Processes Underlying Tmentioning
confidence: 62%
“…Uncovering species coexistence in microorganism communities is an enduring challenge and large gap for microbial ecologists. Co-occurrence networks often reveal non-random co-variation patterns which may re ect community organization -such as direct interactions [19] or shared guilds or niches, and provide a tool for investigating ecological concepts which are di cult to assess in microbial communities [20][21][22]. Under this approach, interactive taxa are linked together either positively or negatively indicating mutualistic or antagonistic co-occurrence patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Network analysis has been used to explore microbial interactions and/or symbiotic patterns among different microbial taxa in various environments [20][21][22]. Furthermore, by identifying the most connected microbial populations or analyzing the effects of nodes and linkages of different methods, network analysis could also identify keystone species that may have the greatest impact on microbial community structure and potential functions [19][20][21][22][23]. A previous study showed that the core microbes with abundant and ubiquitous characters in mangroves were mostly assigned to Gammaproteobacteria, Deltaproteobacteria, Chloro exi and Euryarchaeota [24].…”
Section: Introductionmentioning
confidence: 99%